ANALISIS SELF DISCLOSURE PADA PENGGUNAAN SECOND ACCOUNT INSTAGRAM DI KALANGAN MAHASISWA UNIVERSITAS SLAMET RIYADI (UNISRI) - Widodo, Triandi Febriansah; Wangi, Maya Sekar; Mahar Rizqi, Fikriana (Solidaritas, 2024)
ABSTRACTThis study aims to determine the form, purpose and impact caused among Unisri students after self-disclosure through a second Instagram account. In this study using qualitative methods with observational data collection techniques, interviews and documentation. In this study, researchers used the theory of Dramaturgy developed by Erving Goffman. The main informants in this study numbered six people with predetermined characteristics. The results showed that the form of self-disclosure carried out was in theform of activities, romance, opinions, and so on. Informants conduct self-disclosure aimed at self-expression, self-clarification, and developing relationships. The impact is in the form of positive and negative impacts. The positive impact is in the form of solutions, suggestions, getting to know yourself better and not disturbing others. While the negative impact caused is addiction, and reduced self-confidence. So that users are expected to be wiser and can limit themselves in using social media by not providing personal data to just anyone. Researchers also remind to pay more attention to things that will be shared on social media, so that no party feels disadvantaged. Keywords : Self Disclosure, Second Account, Instagram